The Inadequacy of Legal Provisions on Workplace Sexual Harassment in Nigeria and Ghana: The Way Forward - Emudainohwo, Emuobo (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2023)
Sexual harassment has been a persistent problem in workplaces in Nigeria and Ghana. The legal provisions in both jurisdictions generally focus on the definition of “sexual harassment” without remedies for the harassment, sanctions, enforcement procedures, anti-sexual harassment policies, complaint procedures, etc., that can control sexual harassment in the workplace. The article examines the scantiness and inadequacy of legal provisions on workplace sexual harassment in Nigeria and Ghana, suggesting a way forward. The doctrinal research method has been deployed, focusing on relevant Nigerian and Ghanaian legal provisions. The article considers the organization theory of sexual harassment, using it as a framework, and then contributes to the discussion by arguing that the inadequacy of local laws on workplace sexual harassment is a possible factor for the prevalence or frequency of workplace sexual harassment. The article recommends comprehensive legal provisions to control workplace sexual harassment. Relying on some of the items in the guidelines made by the Indian Supreme Court on workplace or work premises sexual harassment in the case of Vishaka v State of Rajasthan, the article suggested using a comprehensive law that can control workplace sexual harassment. If the suggestions are followed, the incidences of sexual harassment will reduce drastically in workplaces in Nigeria and Ghana. Workplace or work premises sexual harassment in Nigeria and Ghana and the relevant legal provisions have been used to set the article’s limit and to project the discussion herein.DOI: https://doi.org/10.22304/pjih.v10n3.a4